2005
DOI: 10.1016/j.asj.2005.01.015
|View full text |Cite
|
Sign up to set email alerts
|

DMSO: Applications in plastic surgery

Abstract: The authors point out that dimethyl sulfoxide (DMSO) increases tissue perfusion and may effectively treat or prevent ischemia in flaps. They recommend application of topical DMSO every 4 to 6 hours, until blood flow improves, to areas that show signs of ischemia or less than adequate perfusion. Other potential cosmetic surgery uses of DMSO include areas of skin care, pain relief, and treatment of keloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…It is also shown that DMSO counteracts ischemia after trauma. 7 However, the effect of DMSO on pulmonary contusions has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…It is also shown that DMSO counteracts ischemia after trauma. 7 However, the effect of DMSO on pulmonary contusions has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Decrease of serum MDA following DMSO therapy in rat model of GS-induced nephrotoxicity may be due to inhibition of ROS or increase of renal tissue antioxidant enzymes. In addition, our results may be contributed to hydroxyl scavenging property of DMSO (18).…”
Section: Discussionmentioning
confidence: 61%
“…DMSO showed antioxidant and anti-inflammatory properties in many studies (9)(10)(11)(12). DMSO molecule has free electron pairs that makes it a powerful receptor of free radicals, especially hydroxyl radical (18).…”
Section: Discussionmentioning
confidence: 99%
“…Skin reactions (redness, wealing) have been commonly observed with patients treated with cutaneous applications of 95‐100% DMSO (Swanson ). However, 70‐90% DMSO has been found to be useful in the treatment of patients after cosmetic plastic surgery (Young et al ) and various DMSO‐containing creams are available from online suppliers such as http://www.amazon.com. DMSO can be used for the transdermal introduction of antibiotics, steroids, or other drugs, but it also increases the uptake of pesticides and some viruses.…”
Section: Discussionmentioning
confidence: 99%